In vivo γ‐aminobutyric acid measurement in rats with spectral editing at 4.7T. Issue 6 (3rd December 2015) - Sawiak, Stephen J.; Jupp, Bianca; Taylor, Tom; Caprioli, Daniele; Carpenter, T. Adrian; Dalley, Jeffrey W.
Abstract : Purpose: To evaluate the feasibility of spectral editing for quantification of γ‐aminobutyric acid (GABA) in the rat brain and to determine whether altered GABA concentration in the ventral striatum is a neural endophenotype associated with trait‐like impulsive behavior. Materials and Methods: Spectra were acquired at 4.7T for 23 male Lister‐hooded rats that had been previously screened for extremely low and high impulsivity phenotypes on an automated behavioral task ( n  = 11 low‐impulsive; n  = 12 high‐impulsive). Voxels of 3 × 7 × 4 mm 3 (84 μL) centered bilaterally across the ventral striatum were used to evaluate GABA concentration ratios. Results: Quantifiable GABA signals in the ventral striatum were obtained for all rats. Mean‐edited GABA to n‐acetyl aspartate (NAA) ratios in the ventral striatum were 0.22 (95% confidence interval [CI] [0.18, 0.25]). Mean GABA/NAA ratios in this region were significantly decreased by 28% in high‐impulsive rats compared to low‐impulsive rats ( P  = 0.02; 95% CI [–53%, –2%]). Conclusion: These findings demonstrate that spectral editing at 4.7T is a feasible method to assess in vivo GABA concentrations in the rat brain. The results show that diminished GABA content in the ventral striatum may be a neural endophenotype associated with impulsivity. J. Magn. Reson. Imaging 2016;43:1308–1312.